STRATEGI PEMASARAN PRODUK CICIL EMAS PADA PT BANK SYARIAH INDONESIA KCP PAMULANG RAYA - Mahdiyah Putri Syifa (2022)
The development of the business world, especially banking today makes competition very tight in which every company must try to dominate the market as much as possible so as to achieve the company's desired goals. In this era of development of the business world, companies must present the best products and meet people's purchasing power. Therefore, we need a strategy that must be carried out by the company in selling these products, namely through the use of marketing strategies. Currently, companies must be able to choose and follow appropriate marketing strategies to increase the company's sales volume. Business people can carry out marketing strategies through product strategies, advertising strategies, distribution strategies, and pricing strategies. If it is associated with sales volume, it means that marketing activities have an impact on increasing sales volume in the company. Increasing sales volume is one of the goals of the marketing concept, which means that increasing sales is achieved through customer satisfaction. With these improvements, the company can grow and develop. This final project was prepared with the aim of knowing the increase in sales volume of gold installment products and to find out what marketing strategy implementation was carried out by PT Bank Syariah Indonesia KCP Pamulang Raya